(untitled) (Research, Society and Development, 2020)
Light color after frying and sprouting are the main quality parameters evaluated by the pre-fried potato processing industry. Therefore, the objective of this study was to evaluate the suitability for use by the pre-fried potato processing industry, the cultivars Asterix, Corsica, Edison, Lionheart and Markies through the sprouting and post-frying color of the sticks. For this, the tubers were stored at 8 °C (RH 90% ± 2) for up to 180 days. Sprouting started at 60 days with the exception of ‘Lionheart’, which started sprouting at 120 days. At 150 and 180 days, all cultivars showed large sprouts, but still suitable for the processing industry. Visually, the Asterix cultivar remained in category 3 and the most cultivars in 2. The parameter L * reduced with the storage time in all cultivars, indicating the browning of the sticks, which was accompanied by the reduction of parameter b *, indicating less yellowing. It is concluded that All cultivars can be used by the processing industry after storage at 8 °C for 180 days. These results are important to the process industry due to difficult from storage of tubers under refrigeration in reason of browning during fried.